Second law analysis of natural convection in a CNT-water nanofluid filled inclined 3D cavity with incorporated Ahmed body. (September 2017) - Al-Rashed, Abdullah A.A.A.; Kolsi, Lioua; Kalidasan, Karuppan; Malekshah, Emad Hasani; Borjini, Mohamed Naceur; Kanna, P. Rajesh
Highlights: finite volume based three dimensional numerical simulations. natural convection and entropy generation. inclined cubical cavity filled with nanofluid of CNT - water. 3D vorticity - vector potential formalism. Ahmed Body. Abstract: Entropy generation inside an inclined cubical differentially heated cavity filled with CNT-water nanofluid is evaluated numerically using FVM based on 3D vorticity-vector potential formalism. A conductive Ahmed body is incorporated at the center of the enclosure. The effects of several parameters such as Rayleigh number (10 3 ≤ Ra ≤ 10 5 ), volumetric fraction (0 ≤ φ ≤ 0.05) of nanoparticles, angle of inclination of cavity (0° ≤ α ≤ 180°) and thermal conductivity ratio (0.01 ≤ Rc ≤ 100) on entropy generation are analyzed. The results are elucidated with local and total entropy generations and Bejan number. Entropy generation increases when Raleigh number increases due to buoyancy. Entropy declines when the inclination angle is increased up to 90°, after that entropy generation surges. Graphical abstract: